Genetic analysis of grain yield and agronomic traits of quality protein maize inbred lines and their single-cross hybrids under drought stress and well-watered conditions (2022)
Drought-tolerant maize hybrids are crucial to enhance productivity in West and Central Africa. The objectives of this study were to (i) determine the combining abilities of tropical quality protein maize (QPM) inbred lines, (ii) identify hybrids with outstanding yield performance under drought stress (DS) and well-watered (WW) condi-tions, and (iii) identify drought-adaptive traits for index selection under DS. Seventy-eight hybrids developed from a diallel cross among 13 QPM inbred lines were evaluated under DS and WW conditions. The hybrids differed significantly (p ≤0.05) for grain yield (GY) and other traits. General combining ability (GCA) and specific combining ability (SCA) were significant for GY and other traits. Four hybrids (CRIZEQ-24 ×CRIZEQ-77, CRIZEQ-44 ×CRIZEQ-77, CRIZEQ-14 ×CRIZEQ-49, and CRIZEQ-24 ×CRIZEQ-40) were identified with outstanding GY performance under DS. Days to anthesis, ear aspect, number of ears per plant and plant aspect were important traits for selection under DS.